LiZIP3 is a cellular zinc transporter that mediates the tightly regulated import of zinc in Leishmania infantum parasites. Issue 3 (11th March 2015) - Carvalho, Sandra; Barreira da Silva, Rosa; Shawki, Ali; Castro, Helena; Lamy, Márcia; Eide, David; Costa, Vítor; Mackenzie, Bryan; Tomás, Ana M.
Summary Cellular zinc homeostasis ensures that the intracellular concentration of this element is kept within limits that enable its participation in critical physiological processes without exerting toxic effects. We report here the identification and characterization of the first mediator of zinc homeostasis in Leishmania infantum, LiZIP3, a member of the ZIP family of divalent metal‐ion transporters. The zinc transporter activity of LiZIP3 was first disclosed by its capacity to rescue the growth of Saccharomyces cerevisiae strains deficient in zinc acquisition. Subsequent expression of LiZIP3 in Xenopus laevis oocytes was shown to stimulate the uptake of a broad range of metal ions, among which Zn2+ was the preferred LiZIP3 substrate (K0.5 ≈ 0.1 μM). Evidence that LiZIP3 functions as a zinc importer in L. infantum came from the observations that the protein locates to the cell membrane and that its overexpression leads to augmented zinc internalization. Importantly, expression and cell‐surface location of LiZIP3 are lost when parasites face high zinc bioavailability. LiZIP3 decline in response to zinc is regulated at the mRNA level in a process involving (a) short‐lived protein(s). Collectively, our data reveal that LiZIP3 enables L. infantum to acquire zinc in a highly regulated manner, hence contributing to zinc homeostasis.